Development of Presence Administration Information System Model - Imas Sumiati; Ine Maryane; Setiadin Setiadin; Hari Bustomi (Universitas Sultan Ageng Tirtayasa, 2022)
Presence administration is a series of attempts to conceptualize what is meant by administration, how to improve the things that administration does, how to determine the urgency of what public administrators should do. Presence System is a system application to measure employee performance by collecting a database that functions to support monitoring and performance appraisal as well as to improve the effectiveness and efficiency of services in decision making or decision support systems. The Regional Apparatus Work Unit is the executor of executive functions that must coordinate so that government administration runs well. The legal basis that has been in effect since 2004 for the formation of SKPD is Article 120 of Law no. 32 of 2004 concerning Regional Government. TKT in this study is the level of development level 6. The research method used is a qualitative research method, with a case study approach. In qualitative analysis, case studies use variable analysis tools that have been linked and then analyzed based on observations and interviews. Data collection techniques consisted of literature studies, field studies of the Bandung City Industry and Trade Office, Buah Batu District, Bandung City Research and Development Agency, Bandung City Education and Training Agency, and Regional Secretariat Empowerment Organizations in Bandung City. from Bandung. About Information System for Institutional Presence Administration through observation, interviews, focus group discussions and documentation studies. The target of this research is to make e-RK services in accordance with the Manpower Act, the output is the creation of an electronic performance model based on additional income which of course can be integrated with the main tasks and functions, models, and then intellect. property rights and textbooks.